Poor Clinical Sensitivity of Rapid Antigen Test for Influenza A Pandemic (H1N1) 2009 Virus - Ana Maria Bispo de Filippis; Angelika Helmer; Heike Kirberg; Ulrike Reber; Marcus Panning; Marcel A. Müller; Katja Höfling; Bertfried Matz; Sung Sup Park; Anna Maria Eis-Hübinger (Emerging Infectious Diseases, 2009)
Influenza A pandemic (H1N1) 2009 virus RNA was detected by reverse transcription–PCR in 144 clinical samples from Bonn, Germany. A common rapid antigen–based test detected the virus in only 11.1% of these samples. The paramount feature of rapid test–positive samples was high virus concentration. Antigen-based rapid tests appear unsuitable for virologic diagnostics in the current pandemic.